Studi Ekstraksi Bijih Emas Asal Pesawaran dengan Metode Pelindian Agitasi dalam Larutan Sianida - La Ode Arham; Fika Rofiek Mufakhir; Hendra Saputra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Research on the extraction of gold ore from Pesawaran, , Lampung, Indonesia, was carried out using the agitation leaching method in cyanide solution. This study aimed to obtain information on the use of conventional cyanidation methods for extracting gold from the Pesawaran gold ore. The ore preparation was carried out in the form of crushing, grinding and sieving to obtain samples with fraction sizes of -60 + 100 mesh, -100 +150 mesh, -150 + 200 mesh and -200 mesh. The ore characterization was performed using XRD, XRF, SEM-EDX, and wet chemical analysis. The XRD analysis showed that the main mineral phases were silica, hematite, aluminium hydroxide and orthoclase. The major constituents of the ore were Si (53,628%), Fe (15,996%), K (19,744%) and Al (8,045%). The Au content was determined by wet chemical analysis and was found to be 9.67 ppm. The experimental results show that the highest percentage of gold extraction of 83.33% was obtained using sodium cyanide at a concentration of 1000 ppm, a percent solids of 40% and a grain size of 200 mesh. Higher gold extraction was not achieved despite the use of a high cyanide concentration was probably because the remaining gold was not properly liberated. The results of SEM-EDX analysis showed that the gold grain size was <20 Âµm, while the grinding was performed only to a sieve size of -200 mesh (74 Âµm).